Characteristics, Predictors, and Clinical Outcomes in Heart Failure With Reduced Ejection Fraction According to a 1‐Year Left Ventricular Ejection Fraction Following Sacubitril/Valsartan Treatment - Chan Soon Park; Jiesuck Park; Nan Young Bae; Soongu Kwak; Hong‐Mi Choi; Yeonyee E. Yoon; Seung‐Pyo Lee; Yong‐Jin Kim; In‐Chang Hwang; Hyung‐Kwan Kim (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Optimal medical treatment can lead to improvement in left ventricular ejection fraction (LVEF) in patients with heart failure with reduced EF (HFrEF). We investigated the characteristics, predictors, and outcomes of HFrEF according to the 1‐year LVEF following angiotensin receptor–neprilysin inhibitors therapy (ARNI). Methods and Results Using the STRATS‐HF‐ARNI (Strain for Risk Assessment and Therapeutic Strategies in Patients With Heart Failure Treated With Angiotensin Receptor‐Neprilysin Inhibitor) registry, we identified 1074 patients with HFrEF who took ARNI and underwent baseline and 1‐year echocardiography. Patients were classified as HF with improved ejection fraction (HFimpEF) and persistent HFrEF (perHFrEF) (1‐year LVEF >40% and ≤40%). The primary and secondary outcomes were all‐cause and cardiac mortality from the 1‐year follow‐up. Among 1074 included patients, 498 (46.4%) had HFimpEF, and 576 (53.6%) had perHFrEF. Older age, male sex, and large LV end‐diastolic volumes were positive predictors of perHFrEF, whereas atrial fibrillation and high systolic blood pressure were identified as inverse predictors. Patients with HFimpEF showed lower all‐cause and cardiac mortality rates (both log‐rank P<0.001). In the multivariable analysis, perHFrEF (hazard ratio, 2.402 [95% CI, 1.251–4.610]; P=0.008) was an independent predictor of poor outcomes. The risk of all‐cause mortality decreased as the 1‐year LVEF increased up to 40%; however, no additional risk reduction was observed beyond 40%. Compared with patients taking renin‐angiotensin‐aldosterone system inhibitors in the STRATS‐AHF (Strain for Risk Assessment and Therapeutic Strategies in Patients With Acute Heart Failure) registry, those in the STRATS‐HF‐ARNI registry demonstrated better outcomes in both HFimpEF and perHFrEF. Conclusions Patients with HFimpEF had better prognosis than those with perHFrEF, and ARNI treatment in HFrEF could be more beneficial than renin‐angiotensin‐aldosterone system inhibitors for both HFimpEF and perHFrEF. Registration URL: https://www.who.int/clinical‐trials‐registry‐platform; Unique identifier: KCT0008098.